Intelligent Systems and Human Machine Collaboration Select Proceedings of ICISHMC 2022 - Bhattacharyya, Siddhartha; Koeppen, Mario; De, Debashis; Piuri, Vincenzo (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book constitutes proceedings of the International Conference on Intelligent Systems and Human-Machine Collaboration 2022. The papers consist of research from different domains of human-machine interaction, computer engineering like quantum computational intelligence, big data analytics, the Internet of things, etc. The book includes significant contributions from academia and industry dealing with human-machine interaction both from the theoretical development and the application point of view. It also brings out research articles in interdisciplinary platforms applying human-machine interaction. The book is useful to researchers and practitioners alike.
Landmark identification from low-resolution real-time image pose estimation -- BLUEBOT - A Bluetooth Controlled Robot for Deciding Human Intervention based on the Environment check -- Nirbhaya Naari: An Artificial Intelligence tool for detection of crime against Women -- A Clinical Decision Support System Using Machine Learning To Forecast The Risk Of Chronic Pulmonary Disease And Anthracosis -- Pre-Eclampsia Risk Factors Association with Cardiovascular Disease Prediction and Diagnosing Using Machine Learning -- A Low Resource Machine Learning Approach for Prediction of Dressler Syndrome -- Analysis of Twitter Data for Business Intelligence -- Detection and Classification of Cyber Threats in Tweets towards Prevention -- Artificial Neural Network Design for CMOS NAND Gate Using Sigmoid Function -- A Pioneer Image Steganography Method Using The SOD Algorithm.
Keywords: User interfaces (Computer systems).; Human-computer interaction; Application software; Internet of things; Computational intelligence; User Interfaces and Human Computer Interaction; Computer and Information Systems Applications; Internet of Things; Computational Intelligence